COMPETENCE-BASED RECRUITMENT OF NON CIVIL SERVANT STATE EMPLOYEES FOR THE INTERNAL SECURITY DIVISION, SECRETARIAT GENERAL OF THE HOUSE OF REPRESENTATIVES OF THE REPUBLIC OF INDONESIA - Sugito Dapip Mashur; Bambang Giyanto; Edy Sutrisno (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
The security system stipulated in the Decree of the Leadership of the House of Representatives of the Republic of Indonesia Number 51/PIMP/III/2008-2009 concerning General Guidelines for Security Management in the Office Complex of the House of Representatives of the Republic of Indonesia, is a Standard Operating Procedure that has been implemented so far. The security system applied is a zoning security system with a security level of Very Important Person (VIP). To implement the system and level of security, it requires the support of Pengamanan Dalam personnel who have very good security competence. The research method used is a qualitative approach research method, where the data taken comes from three sources, namely the results of interviews with 14 key informants, namely 2 Members of the People's Legislative Assembly of the Republic of Indonesia, Echelon II Officials, Echelon III, Echelon IV Secretariat general of the House of Representatives of the Republic of Indonesia, and staff who are deemed to know the problem. Apart from that, field observations and document review related to the previous recruitment of internal security personnel. The results of the study have illustrated that the cause of the non-optimal results of Pengamanan Dalam personnel recruitment is the absence of Standard Operating Procedures, the absence of openness in its implementation so as to facilitate irregularities in the recruitment process. The resulting recruitment pattern in order to get competent personnel is, internal and external collaboration with agencies, transparency, clear competency standards and strong supervision and commitment.